Intraoperative portal vein insulin assay combined with occlusion of the pancreas for complex pancreatogenous hypoglycemia: Two cases report. Issue 26 (June 2016) - Yang, Zhiying; Tan, Haidong; Sun, Yongliang; Si, Shuang; Xu, Li; Liu, Xiaolei; Liu, Liguo; Zhou, Wenying; Huang, Jia
Abstract : Abstract: Intraoperative localization and confirmation of complete resection of the hypersecreting tissue are the 2 main challenges in the management of pancreatogenous hypoglycemia. Here, we report our experience with intraoperative portal vein insulin assay combined with occlusion of the pancreas in the management of pancreatogenous hypoglycemia. Clinical courses of 2 patients with biochemical evidence of a pancreatogenous hypoglycemia were studied. The preoperative diagnosis was multiple endocrine neoplasia 1 (MEN-1) and nesidioblastosis, respectively. Rapid intraoperative portal vein insulin assay combined with occlusion of the pancreas was used to localize and confirm complete excision of the hypersecreting tissue. Hypoglycemia was successfully treated in both the patients. In the MEN-1 patient, 2 small tumors in the head of pancreas were not resected, as they were deemed noninsulin secreting by intraoperative portal vein insulin assay, thus avoiding a total pancreatectomy. In the patient with nesidioblastosis, using intraoperative portal vein insulin assay combined with occlusion of the pancreas, an appropriate amount of pancreatic tissue was resected thereby avoiding recurrence and diabetes. This technique may be of particular value in patients with complex conditions such as MEN-1 and nesidioblastosis, to localize and achieve complete resection of hypersecreting pancreatic tissue.